# when simplified, the expression (3^1/3) / ( 3^ -2/3) is..any help is greatly appreciated!=)

*print*Print*list*Cite

Expert Answers

justaguide | Certified Educator

The expression ` (3^(1/3))/(3^(-2/3))` has to be simplified. Use the property `a^x/a^y = a^(x - y)`

`(3^(1/3))/(3^(-2/3))`

=> `3^(1/3 - (-2/3))`

=> `3^(1/3 + 2/3)`

=> `3^(3/3)`

=> `3^1`

=> 3

**The expression **`(3^(1/3))/(3^(-2/3)) = 1`

Student Comments

trilliumblue7 | Student

The answer is 27.

Here is how I solved the problem:

- Look at BEDMAS (brackets,exponents,division,multiplication,addition and subtraction in that order).
- BEDMAS says that you have to start with the first bracket
- Since exponents is next in BEDMAS, you have to solve 3^1 which is 3.
- Then division comes next. 3/3=1
- Follow BEDMAS and do the same for the second bracket.
- Write down the answer after solving for the second bracket. (answer should be a long decimal)
- Then do 1/answer in second bracket
- Your final answer should be 27.

Here is an easier way to solve the problem: if you have a good scientific calculator that follows BEDMAS, you can type the question like it is and you will get the right answer.

Please let me know if this helped you.